A Comparison of Metaphoric Expressions Comprehension in Mainstreaming Students with Severe Hearing Impairment and Hearing Students of Junior High School - Reyhaneh Mohammadi; Tahereh-Sima Shirazi; Reza Nilipour; Mahdi Rahgozar; Abbas Pourshahbaz (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: Many researchers believe hearing impaired people suffer from special disability in metaphor comprehension. This study was aimed to compare the comprehension of metaphoric expressions in mainstreaming sever hearing impaired and normal students of junior school in order to determine the source of metaphor comprehension impairment and find whether is this impairment due to their educational environment? Materials & Methods: In this cross-sectional and comparative study, 50 hearing student and 25 hearing impaired student were selected by simple randomized method and tested by two researcher made tasks. All examinee did non metaphoric words task. If they answered more than 75 percent of words correctly and they had all of inclusion criteria, metaphoric expression comprehension task was performed. Then the data were analyzed by statistical tests such as Independent sample T test and one way ANOVA. Results: Mainstreaming hearing impaired students showed difference significantly in score of comprehension of metaphoric expressions (P<0/001). The numbers of literal incorrect answers were more than meaning incorrect answers in mainstreaming hearing impaired students. There were no significant differences between score of comprehension of metaphoric expressions task in first, second and third grade of junior high school in normal hearing students (P=0.401) and mainstreaming hearing impaired students (P=0.120). Conclusion: Incorrect answers of mainstreaming hearing impaired students to test showed their incomplete comprehension from metaphoric expressions and significant difference between hearing impaired students and normal peers in comprehension of metaphoric expressions showed the educational environment of mainstreaming schools is not enough for understanding metaphoric expressions.